SCIENTIFIC WRITING TRAINING FOR STUDENTS OF IBNU SINA SENIOR HIGH SCHOOL - Prayitno, Budi; Wany, Eva; Yustie, Renta (Antis-publisher, 2026)
Objective: This study aims to address the lack of formal instruction in scientific research methods at the elementary and secondary school levels by enhancing students’ scientific writing skills, enabling them to produce well-structured and academically sound scientific articles. Method: The activity was conducted through a community service–based training program employing interactive lectures, guided practice, and mentoring sessions. The training introduced fundamental concepts of scientific research, including problem formulation, use of scientific methods, data interpretation, and systematic scientific writing. Participants were senior high school students who engaged in step-by-step writing exercises and received feedback on their drafts. Results: The training demonstrated a positive improvement in students’ understanding of scientific research principles and their ability to organize ideas into coherent scientific articles. Students showed increased confidence in applying rational and empirical thinking, structuring manuscripts, and using appropriate academic language. Novelty: This program offers a structured and early-stage intervention model for scientific writing at the secondary school level, integrating research method literacy with practical writing skills, which are typically only emphasized at the university level. This approach contributes a novel framework for strengthening pre-university scientific literacy and academic writing competence.